Solve for a 11a-6+2a-3=10a-3+2a

Math
11a-6+2a-3=10a-3+2a
Simplify 11a-6+2a-3.
Tap for more steps…
Add 11a and 2a.
13a-6-3=10a-3+2a
Subtract 3 from -6.
13a-9=10a-3+2a
13a-9=10a-3+2a
Add 10a and 2a.
13a-9=12a-3
Move all terms containing a to the left side of the equation.
Tap for more steps…
Subtract 12a from both sides of the equation.
13a-9-12a=-3
Subtract 12a from 13a.
a-9=-3
a-9=-3
Move all terms not containing a to the right side of the equation.
Tap for more steps…
Add 9 to both sides of the equation.
a=-3+9
Add -3 and 9.
a=6
a=6
Solve for a 11a-6+2a-3=10a-3+2a

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top